Prior Experiences With Racial Discrimination Predict Psychological Reactions to a Recent Incident of Race-Based Rejection Among African American University Students. Issue 2 (17th February 2019) - Sheehan, Brynn E.; Derlega, Valerian J.; Maduro, Ralitsa S.; Winstead, Barbara A.
Abstract: Based on previous theory and research suggesting that a defensive motivational system (DMS) is activated in response to a specific incident of racial discrimination, prejudice, or stereotyping, we examined how prior experiences with racial discrimination increase intense psychological reactions to a recent incident of race-based rejection. Participants were 161 African American undergraduate students from a PWCU or a HBCU who initially completed a Time 1 measure about their prior experiences with racial discrimination. At Time 2, participants who reported being the target of prejudice in the previous 10 to 12 weeks completed measures of thought intrusions about the incident, negative affect about what happened, and lack of forgiveness for the perpetrator. The results indicated that prior exposure to racial discrimination was associated with an increase in thought intrusions about the incident. In turn, more thought intrusions were associated with more negative affect and lower forgiveness for the perpetrator.